Analisis Kesulitan Guru Dalam Merancang Pembelajaran Tematik di Kelas Tinggi SDN 71 Maccini Kabupaten Soppeng - anisa gala; Abd Hafid; sudirman sudirman (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
: The problem in this study is that there are still many teachers who have not been able to design thematic learning in accordance with the provisions of the 2013 curriculum, especially in designing lesson plans, teaching materials, and LKPD. This research is a qualitative descriptive research. Which aims to find out the difficulties of teachers in designing thematic learning. The results showed that in designing lesson plans, teachers had difficulties in combining themes, teachers had difficulties in formulating indicators, and teachers had difficulties in choosing learning models. In the LKPD, the teacher has difficulty in choosing the type of material and presenting interesting images. In teaching materials the teacher has difficulty in entering the material. So, the conclusion is that the implementation of the 2013 Curriculum at SDN 71 Maccini schools is good but the teachers still have difficulty in combining themes, formulating learning indicators, choosing learning models, selecting types of material into the LKPD, inserting interesting pictures into the LKPD, and difficulty in inserting material into teaching materials